Aktualisasi Sila Persatuan Indonesia dalam Semangat Gotong Royong Bangsa - Maria Hermina Bhebhe; Aprilia W. Bhoko Fao; Yohana Elma Sarina Ito Wea; Maria Fransiska Manggus; Sisilia Sela; Maria Eleonora Lejo (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
This research aims to examine and analyze the actualization of the third principle of Pancasila, namely "Unity in Indonesia," in the context of the spirit of gotong royong, which is a noble tradition of the Indonesian nation. Gotong royong, emphasizing cooperation and togetherness, plays a crucial role in strengthening unity amidst the social, cultural, and religious diversity in Indonesia. This study focuses on how the values of unity can be manifested in gotong royong practices across various sectors of life, both at the community level, within government, and in international relations.The methodology employed in this research is a qualitative approach that includes literature studies and interviews with various parties directly involved in gotong royong activities, both in communities and governmental institutions. The research also analyzes various cases that illustrate the implementation of the spirit of gotong royong in everyday life, particularly in addressing social, economic challenges, and natural disasters.The findings indicate that the spirit of gotong royong plays a vital role in reinforcing the unity of the Indonesian nation. Through gotong royong, communities can support each other in facing various social issues while strengthening social bonds among citizens, regardless of existing differences. On the other hand, this study also identifies challenges faced in actualizing the principle of Unity in Indonesia within the spirit of gotong royong, such as the growing individualism in society and widening social gaps.This research is expected to contribute to understanding the importance of actualizing the principle of Unity in Indonesia in national life and to provide recommendations for strengthening the spirit of gotong royong to create a more united, just, and prosperous Indonesia. The spirit of gotong royong, which is an integral part of Indonesian national identity, needs to be continuously developed to face the challenges of modern times and increasingly complex global dynamics.